2020
DOI: 10.3390/en13246481
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Study of a Hybrid Photovoltaic Thermal (PVT) System Coupled with a Domestic Hot Water (DHW) Storage Tank

Abstract: Photovoltaic-thermal panels are hybrid systems that combine the two types of conventional solar energy technologies (photovoltaic and thermal panels) and simultaneously generate both thermal and electrical energy in a micro-cogeneration system. Like any co-generation system, there is an optimal balance that can be achieved between the thermal and electrical energy produced. For this reason, it is important to establish the relationship and inter-connection between the two. Limited research is available on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The effect of the PV/T cell temperature versus the electrical power generated by the PV/ T cell was plotted in Figure 17 for different values of R se . Similar results are found in a parametric study of a PVT system coupled DHW on the electrical power variation as a function of the cell temperature (Barbu et al, 2020).…”
Section: Simulation Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The effect of the PV/T cell temperature versus the electrical power generated by the PV/ T cell was plotted in Figure 17 for different values of R se . Similar results are found in a parametric study of a PVT system coupled DHW on the electrical power variation as a function of the cell temperature (Barbu et al, 2020).…”
Section: Simulation Results and Discussionsupporting
confidence: 85%
“…The results indicated that the variation of JEDT 21,5 the output flow to the customer has the most significant impact on electrical efficiency. The second-highest impact factor is the tank size with a variation (Barbu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Possible improvements in electrical and/or thermal yield through adjustments in cooling structures [12][13][14][15][16] or by varying the cooling fluid [17,18] have also been investigated. Some studies also addressed the impact of the flow rate on the performance of PVT systems [1], through absorber type variation [19,20], the addition of phase change materials [21], the usage of nanofluids [2] or the combination with domestic hot water tanks [22] or hydrogen production [23]. Such a variable flow rate in PVT systems shows two possible effects: first, an increased electrical yield of the PVT system and second, a controllable temperature level of the cooling fluid [24].…”
Section: Existing Studiesmentioning
confidence: 99%
“…Other studies [14,15] have examined the influences of various external parameters, such as geometrical, thermo-physical, and electrical properties, climate conditions, and the thermal parameters of the installation (i.e., tank size, consumer demand curve, temperature at the inlet of the cold water main and outlet flow of the tank) on the performance of PVT system, highlighting the significant impact of the consumer demand curve.…”
Section: Introductionmentioning
confidence: 99%